2009
DOI: 10.1002/adfm.200801117
|View full text |Cite
|
Sign up to set email alerts
|

pH‐Responsive Flower‐Type Micelles Formed by a Biotinylated Poly(2‐vinylpyridine)‐block‐poly(ethylene oxide)‐block‐poly(ε‐caprolactone) Triblock Copolymer

Abstract: In the present work, a method is proposed to assemble pH‐responsive, flower‐like micelles that can expose a targeting unit at their periphery upon a decrease in pH. The micelles are composed of a novel biotinylated triblock copolymer of poly(εε‐caprolactone)‐block‐poly(ethylene oxide)‐block‐poly(2‐vinylpyridine) (PCL‐b‐PEO‐b‐P2VP) and the non‐biotinylated analogue. The block copolymers are synthesized by sequential anionic and ring‐opening polymerization. The pH‐dependent micellization behaviour in aqueous sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 61 publications
1
33
0
Order By: Relevance
“…Our study showed an inhibition of complement activation by BSA or DG loading inside NP + , which might be compared to inhibition obtained after long chain of poly(ethylene glycol) (PEG) addition to strong activator nanoparticles, as shown by Van Butsele et al, Aqil et al and Layer et al (48)(49)(50)(51). Indeed, PEG create a steric barrier around particles able to protect against protein adsorption due to a decrease of surface hydrophobicity and a neutralization of surface potential.…”
Section: Complement Activationsupporting
confidence: 47%
“…Our study showed an inhibition of complement activation by BSA or DG loading inside NP + , which might be compared to inhibition obtained after long chain of poly(ethylene glycol) (PEG) addition to strong activator nanoparticles, as shown by Van Butsele et al, Aqil et al and Layer et al (48)(49)(50)(51). Indeed, PEG create a steric barrier around particles able to protect against protein adsorption due to a decrease of surface hydrophobicity and a neutralization of surface potential.…”
Section: Complement Activationsupporting
confidence: 47%
“…It is known that not all ligands on micelles are required for effective cell targeting. [ 29 ] The excessive addition of functional accessory did not further improve phototriggered uptake of fundamental micelles but led to un-specifi c intracellular accumulation. So 10p seems to be a better formula than 20p.…”
Section: Phototriggered Cellular Uptakementioning
confidence: 99%
“…In relation to the pH, a new structure is described, referred to as a semi-flower-like structure. It is reported that the P2VP couldn't really reach the inner PCL core and hydrophobic clusters of P2VP are formed beneath the curved PEO chains rather than being mixed with PCL in the micelle core [50].…”
Section: Spherical Micellesmentioning
confidence: 99%